Recent Advances in Polysaccharides from Cornus officinalis: Extraction, Purification, Structural Features, and Bioactivities - Shengfang Wang; Baotang Zhao; Xuemei Ma; Jing Zhang; Guofeng Li; Mingze Li; Qi Liang (Foods)
Cornus officinalis, as a medicinal plant, is rich in biologically active components, including polysaccharides, flavonoids, triterpenoids, and organic acids, which offer a variety of health benefits and significant potential for development in the food and pharmaceutical industries. Cornus officinalis polysaccharides (COPs) are considered among the primarily functional ingredients of the plant and are abundant in bioactivities. The present paper reviews the research conducted on the extraction, purification, structural properties, and biological activities of COPs. It also provides an overview of future development prospects, with a view to offering reference material for further development and research on COPs. In addition, the paper makes recommendations regarding theoretical preparations for the exploration of the application potential of COPs in the food industry and various other industrial fields.